Reconstructing spatial planning law through legal discourse: Adaptive Agrarian spatial governance and socio-ecological heritage in Indonesia - Soediro; Kartini, Ika Ariani; Wicaksana, Prasetyo Budi; Saefudin, Yusuf (Research Journal in Advanced Humanities, 2026)
Agricultural land conversion in Indonesia is usually framed as a failure of regulatory coherence and enforcement. This explanation is incomplete because it overlooks how legal and policy language constructs farmland as developable space, investment territory, food-producing land, digital-spatial data, or socio-ecological heritage. This study examines the hierarchy among those competing meanings and reconstructs spatial planning law through the Adaptive Agrarian Spatial Governance Theory (AASGT). It employs critical legal discourse analysis within a qualitative socio-legal design, combining a discourse-historical reading of Indonesian spatial-planning, sustainable-farmland, food, environmental, investment, and geospatial instruments with verified official statistics, peer-reviewed empirical evidence, and contrastive references to Japan, South Korea, and the Netherlands. The analysis identifies five intersecting formations: developmentalism, food security, constitutional-ecological responsibility, technocratic spatialism, and agrarian-community knowledge. Developmentalist and technocratic discourses acquire the greatest decisional authority because they translate land into economically convertible and administratively measurable space. Food-security commitments, ecological rights, and local agrarian knowledge remain visible but are less capable of constraining permits and spatial exceptions. AASGT addresses this imbalance through constitutional-ecological stewardship, intergenerational food justice, socio-ecological heritage, adaptive legality, digital-spatial accountability, economic counterweights, and participatory multilevel governance. The study contributes to legal and environmental humanities by demonstrating that land conversion is sustained by regimes of meaning and authority as well as by regulatory weakness.